ASSESSING CREATIVE THINKING SKILLS OF MTs STUDENTS IN SOLVING RENEWABLE ENERGY PROBLEMS A BINOMIAL TEST ANALYSIS - Kurnia, Mega; Akhsan, Hamdi; Kistiono, Kistiono (Universitas Negeri Padang, 2025)
This study aims to analyse the proportion of creative thinking ability of MTs students on the topic of renewable energy using binomial test statistics. Students' creative thinking ability was measured based indicators of Torrance Tests of Creative Thinking (TTCT): fluency, flexibility, originality, and elaboration. The sample consisted of 109 students selected from four MTs in South OKU District selected by random sampling. The research instrument was in the form of multiple choice questions which were previously tested for validity using the Rasch Item Fit Model analysis and instrument reliability of 0.55. Although not a very high value, this result can still be used for exploratory purposes in the evaluation of the instrument. The data were then analysed using the binomial test with an expected proportion of 50%. The binomial test is used because the data is dichotomous. Results indicated that the highest average score was achieved in fluency (60.54), while the lowest was in originality (22.52). Only 36% of students who can answer more than 50% of the questions correctly, while 64% of students have not managed to reach the expected standard. The binomial test results indicated that the proportion of students who were able to solve renewable energy problems creatively was significantly lower than the expected value (p = 0.004 < 0,05). This finding suggests that students' creative thinking skills are still uneven, influenced by factors such as teacher-centred learning methods, lack of practical exploration, and limited understanding on the topic of renewable energy.